Climate Change and the Church: An Eschatological Perspective - Samuel Izidor; Andrew A. Igwe (Randwick International of Social Science Journal, 2022)
Man has had various form of religious belief, worship and teaching on the origin of the earth and man. This background has accounted for the variant culture and response to nature, the environment and climate change and relationship with believed Creator. Judaic religion and its offshoot of Christian religion constitutes a body of believers and worshippers that have established a belief system and teaching on the origin of man and the earth to which they have ascribed to the creative power of a supreme being known among them as the Almighty God. Some other religions have worshipped the elements and forces of nature eg the sun, moon, stars, mountains, rivers, wind etc that themselves greatly influence the environment and climate. Climate change is the net effect of recorded weather conditions over a given period of time regarding atmospheric conditions, temperature variations, meteorological and earth structural changes etc measured in regularity and pattern. Eschatology is the Christian believe in the events that will culminate in the end of life forms on earth. Climate change and religion are as old as man and coexist. This study examines this relationship with reference to eschatology. Climate change is caused either by the activities of naturaly occurring events of the elements or the activities of man. The system approach and empirical exposition on the doctrine of eschatology as propagated by the Church vis-à-vis climate change effects was adopted. Study outcome have pointed to a clear relationship between climate change and church teaching on eschatology.